Eksplorasi Peran Konsultan Bisnis dalam B2B untuk Penyaluran FDI di Batam-Bintan: Studi Kasus PT Akses Indonesia Nusantara - Muhammad Rayhan Satria; Dwiki Prayoga; Reza Yahnu Dafaridzy (Publikasi Inspirasi Indonesia, 2024)
This study analyzes the role of business consultants in facilitating Foreign Direct Investment (FDI) in the Batam-Bintan region, focusing on PT Akses Indonesia Nusantara as a case study. The region holds significant potential as a strategic investment hub in Southeast Asia due to its geographical advantages, status as a Free Trade Zone (FTZ), and developing infrastructure. However, various challenges, such as regulatory complexity, weak inter-agency coordination, and competition from other ASEAN countries, hinder the attraction of FDI. Through a Business-to-Business (B2B) approach, business consultants serve as strategic intermediaries between foreign investors and local governments. PT Access Indonesia Nusantara provides comprehensive consulting services, including legal guidance, market analysis, and strategic relationship facilitation. Innovative programs like Travel & Learn are among the key strategies to enhance investors’ understanding of local potential while strengthening collaboration with stakeholders. The findings indicate that effective B2B relationships can overcome bureaucratic barriers, expedite licensing processes, and increase investment attractiveness in the Batam-Bintan region. This study recommends regulatory harmonization, improved bureaucratic transparency, and synergy between the government and private sector to maximize foreign investment potential. These measures will enable Batam-Bintan to maintain its position as a competitive investment destination in Southeast Asia and contribute to sustainable national economic growth.